Immunodominant protein MIP_05962 from Mycobacterium indicus pranii displays chaperone activity. (10th April 2017) - Sharma, Ashish; Equbal, Md. Javed; Pandey, Saurabh; Sheikh, Javaid A.; Ehtesham, Nasreen Z.; Hasnain, Seyed E.; Chaudhuri, Tapan K.
Abstract : Tuberculosis, a contagious disease of infectious origin is currently a major cause of deaths worldwide. Mycobacterium indicus pranii ( MIP ), a saprophytic nonpathogen and a potent immunomodulator is currently being investigated as an intervention against tuberculosis along with many other diseases with positive outcome. The apparent paradox of multiple chaperones in mycobacterial species and enigma about the cellular functions of the client proteins of these chaperones need to be explored. Chaperones are the known immunomodulators; thus, there is need to exploit the proteome of MIP for identification and characterization of putative chaperones. One of the immunogenic proteins, MIP_05962 is a member of heat shock protein (HSP) 20 family due to the presence of α‐crystallin domain, and has amino acid similarity with Mycobacterium leprae HSP18 protein. The diverse functions of M. leprae HSP18 in stress conditions implicate MIP_05962 as an important protein that needs to be explored. Biophysical and biochemical characterization of the said protein proved it to be a chaperone. The observations of aggregation prevention and refolding of substrate proteins in the presence of MIP_05962 along with interaction with non‐native proteins, surface hydrophobicity, formation of large oligomers, in‐vivo thermal rescue of Escherichia coli expressing MIP_05962, enhancing solubility of insoluble protein maltodextrin glucosidase (MalZ) under in‐vivo conditions, and thermal stability and reversibility confirmed MIP_05962 as a molecular chaperone. Abstract : Mycobacterium indicus pranii ( MIP ) is gaining attention as a possible vaccine candidate. Thus, it is pertinent to characterize the proteome of this nonpathogen. Physicochemical characterization of MIP_05962 has validated it as a chaperone. Higher survival of Escherichia coli expressing MIP_05962 after heat shock corroborated our hypothesis. Understanding multiple roles of chaperones can unravel novel targets to treat TB.